INTEGRASI STEM DALAM PEMBELAJARAN MATEMATIKA: DAMPAK TERHADAP KOMPETENSI MATEMATIKA ABAD 21 - Veni Saputri; Tatang Herman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The use of new educational approaches and technologies can be beneficial in integrating 21st century skills and core competencies in education. STEM provides students with an effective learning environment to improve math skills and other 21st century skills. This research aims to explore and synthesize the best stem applications in math learning and its impact on 21st century mathematical competence. There are several studies related to the integration of STEM in mathematics learning to improve 21st century mathematical competence, which includes critical thinking and problem solving, creativity, communication skills, and ability to work collaboratively. The search for relevant data base was conducted in a study published from 2017 to 2021 that examined STEM and 21st century math competencies in formal education. The search strategy was carried out systematically by reviewing articles in the field of Education that had been published in the ERIC, Scopus, PubMed, Science Direct, and Google Scholar databases. Based on the results of systematic reviews of the literature generated that integrating STEM in mathematical learning must pay attention to the content of the lesson, the methods used in learning must be problem-based and project-based, and learning must be cooperative. In addition, STEM integration in math learning tends to improve 21st century mathematical competence especially in critical thinking and problem solving skills